Activity of pemetrexed-based regimen as first-line chemotherapy for advanced non-small cell lung cancer with asymptomatic inoperable brain metastasis: a retrospective study. (August 2015) - Zhu, Weiyou; Røe, Oluf Dimitri; Wu, Chen; Li, Wei; Guo, Renhua; Gu, Yanhong; Liu, Yiqian; Shu, Yongqian; Chen, Xiaofeng
<x content-type="archive" xml:space="preserve">Abstract</x> This retrospective study was conducted to assess the efficacy of combination of pemetrexed and cisplatin/carboplatin as first-line treatment in inoperable and asymptomatic brain metastasis (BM) from non-small cell lung cancer (NSCLC). A total of 30 patients with adenocarcinoma were included. Nine patients had solitary, and 21 patients had multiple BM. At evaluation after two cycles, the complete response (CR) rate, partial response (PR) rate, and stable disease (SD) for brain lesions was 0, 33.3, and 46.7%, respectively. The overall CR, PR, and SD were 0, 23.3, and 46.7%, respectively. The median time to tumour progression of BM (TTP-BM) was 6.0 months (95% CI 4.068–7.932). The median progression-free survival (PFS) and overall survival (OS) were 5.0 months (95% CI 4.197–5.803) and 11.0 months (95% CI 7.398–14.602), respectively. Pemetrexed has comparable activity on brain lesions as on extracranial tumours in advanced lung adenocarcinoma patients with inoperable and asymptomatic BM.